The application by the legislator of the regime of administrative responsibility in light of the jurisdiction of the Constitutional Tribunal of the Republic of Poland - Karciarz, Mateusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
Recently, there has been a noticeable tendency to replace the regime of criminal responsibility with administrative responsibility. Administrative responsibility is objective in nature and has a repressive and ordinal character, detached from guilt. The Constitutional Tribunal, in its jurisdiction, states many times that the regime of liability applied by the legislator depends only on its choice. The Tribunal does not control the desirability or appropriateness of the adopted solutions. The task of the Constitutional Tribunal is only to provide an assessment, if the solutions adopted by the legislator do not violate constitutional norms and values, such as, among others, the principle of proportionality,or the ne bis in idem principle.